KINETICS AND MECHANISM OF ALKALINE KMNO4 OXIDATION OF D-SORBITOL AND D-DULCITOL - Latona, Dayo Felix; Akinola, Adegoke Emmanuel (Global Journal of Chemistry, Biology and Physics (GJCBP), 2023)
The kinetics and mechanism of alkaline KMnO4 oxidation of D-sorbitol and D-dulcitol were investigated in this study. The oxidation reactions of sugar alcohols were studied using potassium permanganate in alkaline medium. The kinetics of the reaction were found to be inverse first order with respect to sugar alcohol for both substrates, first order each with respect to [KMnO4] and [OH-], and independent of ionic strength for both substrates investigated. Activation parameters such as activation energy (Ea), enthalpy of activation (ΔH*), and entropy of activation (ΔS*) were obtained. The oxidation reaction of sugar alcohols was found to exhibit substrate inhibition due to the formation of a 1:1 manganese-sugar alcohol complex that resists oxidation. A plausible mechanism was proposed based on kinetic and spectroscopic studies. The proposed mechanism involves the formation of an intermediate complex between the sugar alcohol and KMnO4 followed by a series of reactions that ultimately lead to the formation of the final products. The results obtained from this study provide insights into the kinetics and mechanism of alkaline KMnO4 oxidation of sugar alcohols and contribute to the understanding of the oxidation of these compounds.